A Study Assessing Prescribing Quality Of Universiti Sains Malaysia’s Primary Care Providers And Evaluation Of Its Impact Using Andersen’s Model And Propensity Score Method - Al-Dahbali, Abdullah Ahmed Hassan (2010)

(untitled)
Escalation of healthcare cost is a world-wide problem. Assessing and improving the quality of healthcare services should be a part of any agenda for healthcare reforms and cost containment. Drug prescribing is one of healthcare services that requires continuous assessment and improvement. However, available tools for assessing prescribing appropriateness have many shortcomings including lack of predictive validity. This study evaluates the prescribing pattern of Universiti Sains Malaysia’s (USM’s) primary healthcare providers. USM offers primary healthcare services to its beneficiaries. The evaluation was performed at a macro level where the core prescribing indicators and the defined daily dose (DDD) methodologies adopted by the World Health Organization (WHO) were calculated from an academic year data of service users.